2020
DOI: 10.1002/eji.202048582
|View full text |Cite
|
Sign up to set email alerts
|

GILZ in sepsis: “Poor is the pupil who does not surpass his master”

Abstract: With the legendary saying of Leonardo da Vinci in the title, we suggest that Glucocorticoid Induced Leucine Zipper (GILZ) may have more promising effects against polymicrobial sepsis, than glucocorticoids (GC). Indeed, the use of GCs in sepsis remains a matter of debate. The rationale for their use in sepsis is to modulate the exaggerated inflammatory response while maintaining innate immunity. However, GC resistance and side‐effects limit their therapeutic value in sepsis. Hence, there is a growing interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…This combination therapy will be further discussed below. Alternatively, administration of GC-induced proteins, such as GILZ, allows working downstream of the GR and thus provides a potential mechanism to circumvent GCR in sepsis (54,55,103). Injection of a TAT-GILZ fusion construct into mice has been shown to protect against LPS-induced endotoxemia (31).…”
Section: Glucocorticoid Resistance In Sepsismentioning
confidence: 99%
“…This combination therapy will be further discussed below. Alternatively, administration of GC-induced proteins, such as GILZ, allows working downstream of the GR and thus provides a potential mechanism to circumvent GCR in sepsis (54,55,103). Injection of a TAT-GILZ fusion construct into mice has been shown to protect against LPS-induced endotoxemia (31).…”
Section: Glucocorticoid Resistance In Sepsismentioning
confidence: 99%
“…Based on their collective findings, authors propose an essential role for GILZ, and monocytes/macrophages, in pathogenesis of septic shock. Indeed, given the limitations of glucocorticoids (e.g., adverse effects and resistance), it is suggested that that GILZ-based options (e.g., cell-permeable GILZ, synthetic GILZ-derived peptide, CRISPRbased transcriptional activators) may represent viable treatment modalities for treatment of sepsis (Vandewalle and Libert, 2020). Studies exploring regulation of macrophage function indicate that GILZ downregulation, via MyD88-dependent and -independent mechanisms, is a consequence of decreased mRNA, reduced translation and/or protein stability, effects promoting macrophage activation (Hoppstädter et al, 2019).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Importantly, the advent of GILZ-based options (e.g., cell-permeable GILZ fusion protein, synthetic GILZ peptide, GILZ-overexpressing mesenchymal stem cells) has raised the prospect of therapeutic GILZ delivery for a variety of conditions with underlying dysregulation of immune and inflammatory mechanisms hoping to avoid deleterious effects associated with the use of glucocorticoids (Flynn et al, 2019;Vandewalle and Libert, 2020). The demonstrated effects of GILZ on immune and inflammatory responses take added clinical relevance and importance given emerging reports that glucocorticoids (e.g., DEXA) can be of benefit for those This article has not been copyedited and formatted.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of NF-kB signaling pathways Short-Chain Alcohols Protect Mice from LPS-induced Septic Shock couples GILZ to membrane-penetrating sequences, is an attractive prospect, although further studies are needed to demonstrate the feasibility and safety of GILZ in clinical setting. Alternatively, the targeted activation of GILZ expression using the CRISPR/dCas9 activator complex specifically in macrophages could be used (96). It should be noted that a peptide targeting the C-terminal region of GILZ 115-137 aa in the mouse GILZ sequence has demonstrated a potential therapeutic effect in experimental autoimmune encephalitis (EAE) (97), which suggesting that diverse regions of GILZ can bind different partner proteins.…”
Section: Prospects Of Gilz In Sepsismentioning
confidence: 99%